2020
DOI: 10.1200/edbk_278853
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Blockade for Prostate Cancer: Niche Role or Next Breakthrough?

Abstract: A number of trials have evaluated the use of single-agent immune checkpoint inhibitors for the treatment of metastatic castration-resistant prostate cancer (mCRPC). The benefit appears to be limited to a small subset of patients, such as those with tumors with microsatellite instability, highlighting the importance of biomarkers to identify which patients may be more likely to respond. Given the lack of efficacy for most patients with mCRPC, our understanding of the mechanisms of primary resistance to checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…11,12 TMB is an emerging, independent biomarker of outcomes with immunotherapy in multiple tumor types, including prostate cancer. 13 However, metastatic prostate cancer generally has a low TMB (median, 2.9 mutations/megabyte), and only 3.0%-8.3% of advanced prostate cancer tumors have a high TMB. 14,15 In the CheckMate 650 trial, treatment with ICIs (ipilimumab and nivolumab) resulted in an objective response rate of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 TMB is an emerging, independent biomarker of outcomes with immunotherapy in multiple tumor types, including prostate cancer. 13 However, metastatic prostate cancer generally has a low TMB (median, 2.9 mutations/megabyte), and only 3.0%-8.3% of advanced prostate cancer tumors have a high TMB. 14,15 In the CheckMate 650 trial, treatment with ICIs (ipilimumab and nivolumab) resulted in an objective response rate of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TMB is an emerging, independent biomarker of outcomes with immunotherapy in multiple tumor types, including prostate cancer. 13 However, metastatic prostate cancer generally has a low TMB (median, 2.9 mutations/megabyte), and only 3.0%–8.3% of advanced prostate cancer tumors have a high TMB. 14 , 15 In the CheckMate 650 trial, treatment with ICIs (ipilimumab and nivolumab) resulted in an objective response rate of 56.3% in patients with a TMB above the median (74.5 mutations/patient); patients with a TMB above the median also had longer radiographic progression-free survival when compared with those with a TMB below the median (7.4 months [95% CI, 6.5 months to not estimated] vs. 2.4 months [95% CI, 1.8–3.9 months], p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Jiao et al. hypothesize that this mechanism is the key factor that explains the lack of clinical efficiency of immunotherapies in metastatic CRPC patients and indicates the potential of immune checkpoint therapy in combination with TGF-β inhibitors ( 285 , 286 ). A recently published study demonstrated that the immunosuppressive microenvironment within PCa bone metastasis can be targeted via the CCL20-CCR6 axis.…”
Section: Disseminating Tumor Cells and Minimal Residual Disease In Prmentioning
confidence: 99%
“…Furthermore, NCT04116775 is evaluating fecal microbiota transplant with pembrolizumab in patients with mCRPC. Other agents that are being evaluated in combination with PD-1-directed therapies in the mCRPC setting include ipatasertib (AKT inhibitor; NCT03673787), isatuximab (anti-CD38 antibody; NCT03367819), naptumomab (5T4-targeted immunotoxin; NCT03983954), GB1275 (CD11b agonist; NCT04060342), utomilumab (4-1BB antibody; NCT03217747), and PF-4518600 (OX40 receptor agonist; NCT03217747) [104].…”
Section: Miscellaneous Agentsmentioning
confidence: 99%